A low-carbon solidifying agent for soft soil foundation deep mixing piles, and a preparation method and construction method thereof
By combining composite cement and admixtures, the problems of high cement cost and carbon emissions in traditional deep mixing piles are solved. The low-carbon curing agent is rapidly consolidated in soft soil foundations and produces high-strength piles, which improves construction efficiency and the impermeability of the piles.
Patent Information
- Application Number
- CN202610947067.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-06-29
AI Technical Summary
Traditional deep mixing pile technology uses cement as a curing agent, which has high cost and high carbon emission problems. Industrial solid wastes such as slag and fly ash have low early strength and slow reaction in soft soil foundations, making it difficult to fully combine with the soil, resulting in uneven pile strength and weak impermeability.
A low-carbon curing agent, consisting of composite cement, slag, fly ash, gypsum, inert mineral admixtures, composite activators, and composite additives, is ball-milled and mixed with water to form a slurry. The early strength development and microstructure optimization are promoted by using a multi-element silicate cement-sulfate-alkali composite activation system and composite acid-modified triethanolamine. The workability and permeability of the slurry are improved by combining a water-reducing, wetting-enhancing, and thickening composite additive system.
It achieves rapid early strength development of low-carbon curing agent, solidifies soil particles into good consolidation, uniformly distributes slurry, and results in high pile strength and excellent impermeability, thereby reducing construction costs and environmental burden.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a low-carbon curing agent for deep mixing piles in soft soil foundations, and its preparation and construction methods. Background Technology
[0002] Soft soil foundations, due to their low strength and large deformation, are prone to problems such as uneven settlement, cracking, and even foundation instability during construction. These problems not only affect the stability and safety of buildings but can also increase the complexity and cost of construction. Therefore, reinforcing soft soil foundations has become one of the key measures to ensure project quality.
[0003] Deep mixing pile technology is a common foundation reinforcement method and has been widely used in the treatment of soft soil foundations. Traditional deep mixing pile technology typically uses cement as a solidifying agent, forcibly mixing it with the underground soil using deep mixing machinery to solidify the soil and utilize the cementitious properties of cement to enhance the soil's strength and stability. However, cement, as a traditional soil solidifying agent, is costly, and its production process emits large amounts of carbon dioxide, increasing the environmental burden and economic pressure on engineering projects.
[0004] In recent years, the preparation of geopolymers or alkali-activated materials using industrial solid wastes such as slag and fly ash has become a research hotspot. However, these materials have the following problems in actual deep mixing pile engineering: First, they have low early strength and slow reaction initiation, making it difficult to meet the requirements of rapid construction; second, in soft clay layers (such as silt and clay), the consolidation between soil particles and cementitious materials is poor, making it difficult for the cementitious materials to fully bond with the soil, resulting in low pile strength and difficulty in achieving the expected reinforcement effect; third, the morphology of industrial solid waste particles such as slag and fly ash differs greatly from that of cement, easily leading to poor slurry fluidity and segregation, making it difficult to distribute evenly in deep mixing and causing uneven pile strength; finally, the pile has weak impermeability, affecting long-term stability. Summary of the Invention
[0005] To overcome the above problems, the present invention provides a low-carbon curing agent for deep mixing piles in soft soil foundations, as well as its preparation and construction methods.
[0006] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a low-carbon solidifying agent for deep mixing piles in soft soil foundations, the raw materials of which comprise, by weight: The composition includes 3-15 parts of composite cement, 30-70 parts of blast furnace slag, 5-20 parts of fly ash, 5-10 parts of composite gypsum, 0.01-10 parts of inert mineral admixture, 0.02-2.5 parts of composite activator, and 0.01-0.08 parts of composite additive. The composite cement includes P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine; the composite acid-modified triethanolamine is triethanolamine modified with phosphorous acid and sebacic anhydride. The composite gypsum includes hemihydrate gypsum and fluorogypsum; The inert mineral admixture includes heavy calcium carbonate powder; The composite activator includes sodium sulfate, red mud, and sodium silicate; The composite additives include polycarboxylic acid, fatty alcohol polyoxyethylene ether, and polyacrylamide.
[0007] In one or more embodiments, the method for preparing the composite acid-modified triethanolamine includes: (1) Disperse triethanolamine, p-toluenesulfonic acid and hydroquinone in toluene, and add sebacic anhydride in batches to carry out esterification reaction; (2) After the esterification reaction is completed, add phosphorous acid, distill under reduced pressure, and collect the fraction at 130~140℃; after cooling to room temperature, filter and collect the filtrate; remove the solvent and dry to obtain triethanolamine modified with composite acid.
[0008] More preferably, in step (1), the mass ratio of triethanolamine to sebacic anhydride is 1:(1~1.5).
[0009] More preferably, in step (1), the mass ratio of triethanolamine, p-toluenesulfonic acid and hydroquinone is 1:(0.045~0.055):0.001.
[0010] More preferably, in step (1), the temperature of the esterification reaction is 110~120℃ and the reaction time is 3~4 h.
[0011] More preferably, in step (2), the mass ratio of triethanolamine to phosphorous acid is 1:(0.5~0.9).
[0012] More preferably, in step (2), the vacuum degree of vacuum distillation is -0.08 to -0.09 MPa.
[0013] More preferably, in step (2), the method for removing the solvent is vacuum distillation.
[0014] In one or more embodiments, the mass ratio of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid hardening sulfoaluminate cement and composite acid-modified triethanolamine in the composite cement is (0.6~0.9):(0.01~0.3):(0.05~0.2):(0.0001~0.0005).
[0015] In one or more embodiments, the method for preparing composite cement includes: ball milling P·O 42.5 ordinary silicate cement, P·O 52.5 ordinary silicate cement, 42.5 rapid-hardening sulfoaluminate cement and composite acid-modified triethanolamine to obtain composite cement.
[0016] Preferably, the ball milling rate is 100~200 r / min, and the ball milling time is 5~10 min; the specific surface area of the composite cement after ball milling is 380~450 m². 2 / kg.
[0017] In one or more embodiments, the blast furnace slag is of grade S95 or higher, and the sum of the contents of SiO2 and CaO is greater than 80%.
[0018] In one or more embodiments, the fly ash is secondary fly ash, and the sum of the contents of SiO2, Al2O3 and Fe2O3 is ≥70.0%.
[0019] In one or more embodiments, the mass ratio of hemihydrate gypsum to fluorogypsum in the composite gypsum is (0.1~0.3):(0.7~0.9).
[0020] In one or more embodiments, the hemihydrate gypsum in the composite gypsum is desulfurized building gypsum, which meets the relevant requirements of GB / T9776-2022 standard; the calcium sulfate content (dry basis) of the fluorogypsum is ≥90%, and the pH is 4.0~8.0.
[0021] In one or more embodiments, the mass ratio of sodium sulfate, red mud, and sodium silicate in the composite activator is (0.05~0.4):(0.6~0.9):(0.01~0.15).
[0022] In one or more embodiments, the red mud in the composite activator is Bayer process red mud with a specific surface area ≥400 m². 2 / kg; Sodium silicate is instant sodium silicate powder with a modulus of 1.0~2.0.
[0023] In one or more embodiments, the mass ratio of polycarboxylate superplasticizer, fatty alcohol polyoxyethylene ether and polyacrylamide in the composite admixture is (0.8~0.95):(0.01~0.1):(0.01~0.1).
[0024] In one or more embodiments, the method for preparing the composite admixture includes: Under nitrogen protection, antioxidant 1010 was added to fatty alcohol polyoxyethylene ether and stirred until dissolved. Then phosphoric acid was added in batches and stirred at 55~65℃ until the system became a uniform viscous liquid. Water was added to the system and stirred until homogeneous. The monoester content was measured to be ≥60%, and the pH of the system was adjusted to 6.5~7.5. The liquid product was collected by vacuum distillation and spray-dried to obtain a powdered enhanced wetting agent. A composite additive is obtained by mixing polycarboxylate superplasticizer, powdered reinforcing wetting agent and polyacrylamide.
[0025] Preferably, the mass ratio of fatty alcohol polyoxyethylene ether to antioxidant 1010 is (0.95~1.05):0.001, more preferably 1:0.001.
[0026] Preferably, antioxidant 1010 is added to the fatty alcohol polyoxyethylene ether, and the stirring temperature is 48~52℃, and the stirring rate is 200~250 r / min.
[0027] Preferably, the time for heat preservation and stirring is 2 to 3 hours.
[0028] Preferably, water is added to the system, and the temperature is 70~75℃ while stirring, and the stirring time is 0.5~1 h.
[0029] Preferably, during vacuum distillation, the vacuum degree is -0.08 to -0.09 MPa and the temperature is 55 to 65°C.
[0030] Preferably, the polycarboxylate superplasticizer, powdered reinforcing wetting agent and polyacrylamide are mixed by stirring at a speed of 50-150 r / min for a time of 5-8 min.
[0031] A second aspect of the present invention provides a method for preparing the low-carbon solidifying agent for deep mixing piles in soft soil foundations as described in the first aspect, comprising the following steps: A low-carbon curing agent for deep mixing piles in soft soil foundations is obtained by ball milling composite cement, blast furnace slag, fly ash, composite gypsum, inert mineral admixtures, composite activators, and composite additives.
[0032] In one or more embodiments, the ball milling rate is 100-200 r / min, and the ball milling time is 10-20 min.
[0033] A third aspect of the present invention provides a method for constructing the low-carbon curing agent for deep mixing piles in soft soil foundations as described in the first aspect, comprising the following steps: S1. The low-carbon curing agent for deep mixing piles in soft soil foundations is mixed with water to form a slurry by feeding materials according to the preset ratio through an automatic metering system. S2. Move the pile driver to the pile position, start the mixing drill, and inject grout into the borehole through the grout delivery device while drilling. When the drill bit of the mixing drill reaches the designed depth, rotate it in the opposite direction to lift the drill bit, and inject grout into the borehole through the grout delivery device while lifting. S3. When the drill bit of the mixing drill reaches the top of the pile, the slurry delivery device is turned off, and the mixing drill resumes drilling for mixing. When the drill bit of the mixing drill reaches the designed depth, it is rotated in the opposite direction to lift the drill bit until it reaches the top of the pile. S4. After the single pile construction is completed, move the machine to the next pile position and cycle through "drilling down and spraying grout - lifting and spraying grout - drilling down and mixing - drilling up and mixing".
[0034] In one or more embodiments, in step S1, the mass ratio of water to the low-carbon curing agent used for deep mixing piles in soft soil foundations is (0.5~0.8):1.
[0035] In one or more embodiments, step S1, the method of mixing a low-carbon curing agent for deep mixing piles in soft soil foundations with water to form a slurry, includes: The low-carbon curing agent used for deep mixing piles in soft soil foundations is dispersed in 50-60% of the total water volume, and the remaining water is added after stirring. The mixture is stirred continuously to obtain slurry.
[0036] Preferably, the stirring and continuous stirring rate is 200~300 r / min; the stirring time is not less than 2 min; and the continuous stirring time is not less than 2 min.
[0037] In one or more embodiments, in step S2, the pressure of the injected slurry is 1.0~3.0 MPa.
[0038] In one or more embodiments, in step S2, the drilling speed of the drill bit of the mixing drill is 0.5~1.0 m / min.
[0039] In one or more embodiments, in step S2, the drill bit of the mixing drill is raised at a rate of 0.5~1.0 m / min.
[0040] The beneficial effects of this invention are as follows: (1) The low-carbon curing agent for deep mixing piles in soft soil foundation provided by the present invention not only develops rapidly in the early stage to meet the needs of rapid construction, but also forms a good consolidation with soil particles; the soil after curing has high strength; furthermore, it can maintain homogeneity and stability during pumping and stagnation without segregation and bleeding; and at the same time has excellent impermeability.
[0041] (2) This invention achieves efficient activation of solid waste activity and directional optimization of microstructure by constructing a synergistic system of "multi-component silicate cement-sulfate-alkali composite activation" and "composite acid-modified triethanolamine functional regulation". In the composite activator, red mud and sodium sulfate jointly create a stable alkaline environment, which rapidly destroys the glassy network of blast furnace slag and fly ash, releasing active silicon, aluminum and calcium ions; at the same time, composite gypsum (hemihydrate gypsum / fluorogypsum) and rapid hardening sulfoaluminate cement work together to provide immediate and continuous sulfate and aluminum sources, promoting the early generation of a large amount of ettringite (AFt) crystal network, rapidly establishing an early strength skeleton, and solving the core problem of low early strength of low carbon system. In particular, the composite acid-modified triethanolamine is uniformly distributed on the surface of the cementitious particles during ball milling. Its phosphate groups (inorganic acid) and sebacic anhydride (organic acid) regulate the morphology of calcium ion dissolution and hydration products through complexation. The triethanolamine groups promote the formation of denser hydrated calcium silicate (CSH) gel. The dual effect significantly refines the pores and blocks the seepage channels, thereby greatly improving the water permeability resistance and long-term durability of the pile from the root.
[0042] (3) This invention fundamentally improves the workability and permeability of the slurry from a rheological perspective by introducing a ternary composite admixture system of "water reduction-enhanced wetting-thickening". The polycarboxylate superplasticizer achieves high dispersion of the curing agent particles at a low water-cement ratio through a strong steric hindrance effect, ensuring that the slurry has excellent high fluidity (initial ≥150 mm). As a highly efficient wetting and penetrating agent, fatty alcohol polyoxyethylene ether can drastically reduce the surface tension of the slurry, making it easy to spread and penetrate deeply in the soil like a "liquid drill bit", greatly improving the uniformity of slurry-soil mixing, especially ensuring the forming quality of deep piles. Polyacrylamide constructs a weak three-dimensional network structure through long polymer chains, effectively locking in free water, providing the necessary thixotropy and anti-settlement ability, ensuring that the slurry remains homogeneous and stable during pumping and stagnation, without the risk of segregation and bleeding. The three work together to provide an ideal slurry with "high fluidity, deep penetration, and high stability" for deep mixing pile construction. At the same time, increasing the spraying pressure can further improve the mixing uniformity of the curing agent slurry and the deeply solidified soil, giving full play to the cementing and solidification effect of the curing agent.
[0043] (4) The reason why the strength of the mixing pile prepared by the traditional cementitious materials for consolidating soil is not high is mainly due to the adsorption and encapsulation of the hydration ions of the consolidating agent by organic matter and clay minerals, which makes it difficult for the hydration products to effectively nucleate, grow and bridge at the soil particle interface. At the same time, the uneven distribution of hydration products and the loose and porous interface transition zone result in weak adhesion between cement hydration gel and soil particles and poor interface bonding, making it impossible to form a continuous and dense cemented structure. In this invention, under a highly alkaline environment, the active silica-alumina components in precursors such as slag and fly ash dissolve and undergo condensation reaction to generate CSH and hydrated calcium aluminosilicate (CASH) gel. At the same time, the alkaline solution undergoes ion exchange and surface activation with the soil particles, reducing the repulsive force between particles and providing reaction sites. With the help of polycarboxylate superplasticizer and high-efficiency wetting and penetrating agent, the in-situ newly formed gel firmly connects the loose soil particles through chemical cementation and physically fills the pores and densifies the structure, ultimately forming an whole with gel as the cementing phase and soil particles as the skeleton, thereby generating and continuously increasing strength.
[0044] (5) This invention uses bulk industrial solid waste as the absolute main material, achieving low carbon and low cost. The total mass proportion of solid waste components such as blast furnace slag, fly ash, red mud and gypsum in the raw materials can reach more than 85%, while the amount of traditional silicate cement used is greatly reduced. This not only significantly reduces the cost of raw materials and production energy consumption from the source, but also realizes the high added value synergistic utilization of various solid wastes. Detailed Implementation
[0045] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0046] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0047] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0048] In the following examples, the blast furnace slag is grade S95, and the combined content of SiO2 and CaO is 85%.
[0049] The fly ash is grade II fly ash, with a combined content of SiO2, Al2O3, and Fe2O3 of 80.0%.
[0050] The calcium sulfate content (dry basis) of fluorogypsum is 92%, and the pH is 6.7.
[0051] In the composite activator, the red mud is Bayer process red mud with a specific surface area of 452 m². 2 / kg; Sodium silicate is instant sodium silicate powder with a modulus of 1.0~2.0.
[0052] Preparation of triethanolamine modified with composite acid: (1) Disperse 1 part triethanolamine, 0.05 parts p-toluenesulfonic acid (as catalyst), and 0.001 parts hydroquinone (as polymerization inhibitor) in toluene at twice the total mass of raw materials, stir (250 r / min) until dissolved, and slowly add 1.25 parts sebacic anhydride in 5 batches over 30 min, controlling the temperature to prevent sudden rise. Raise the temperature of the reaction system to 115℃ and reflux for 3.5 h. Separate water using a water separator. When the acid value of the system is ≤5 mg OH - The esterification reaction is complete when the concentration of esters reaches 1 / g.
[0053] (2) Keep the system temperature at 110℃ and slowly add 0.7 parts of phosphorous acid dropwise over 30 min; after the addition is complete, raise the temperature to 135℃, switch to vacuum distillation apparatus (vacuum degree -0.085 MPa), react for 4.5 h until no distillate is distilled off, and stop the reaction; cool the distillate to room temperature and filter to remove impurities; raise the filtrate to 80℃ and remove residual toluene by rotary evaporation under a micro negative pressure of -0.095 MPa, and dry at low temperature (40℃) under vacuum to obtain a viscous liquid product, and then use centrifugal spray drying method (droplet size 50 μm, air inlet temperature 150℃, rotation speed 15000 r / min) to obtain powdered composite acid modified triethanolamine.
[0054] Homogenization of composite gypsum: Hemihydrate gypsum and fluorogypsum are put into a three-dimensional motion mixer and mixed at 180 r / min for 10 min until homogeneous.
[0055] Homogenization of the composite activator: Sodium sulfate, red mud, and sodium silicate are added to a three-dimensional motion mixer and mixed at 180 r / min for 10 min until homogeneous. The red mud needs to be dried to constant weight at 105±5℃ beforehand.
[0056] Preparation of composite admixtures: (1) Under nitrogen protection, heat 1 part of fatty alcohol polyoxyethylene ether to 50°C and stir (225 r / min). Add 0.001 part of antioxidant 1010 and stir until dissolved. Heat to 55°C and add 0.15 parts of phosphoric acid in 5 batches, with an interval of 10 min between each batch. The total feeding time is controlled between 1 and 1.5 h. After the addition is complete, keep warm at 60°C and stir for 2.5 h. Take a sample every 30 min until the system is a uniform viscous liquid without particles.
[0057] (2) Add 0.3 parts of deionized water to the system within 15 min, heat to 70℃ and stir for 1 h; determine the monoester content by potentiometric titration until it reaches ≥60%, if it does not reach the standard, add water and keep warm for another 30 min. Cool to below 40℃ and adjust the pH to 7.0 by adding 30% sodium hydroxide solution. (3) Remove trace amounts of water and low-boiling substances by vacuum distillation at -0.085 MPa and 60℃ for 1 h, cool to room temperature to obtain liquid product, transfer the liquid product to spray drying tower, and spray dry to obtain powdered enhanced wetting agent.
[0058] (4) Mix 0.9 parts of polycarboxylate superplasticizer powder, 0.05 parts of powdered reinforcing wetting agent and 0.05 parts of polyacrylamide at low speed (100 r / min) for 6.5 min to obtain composite admixture.
[0059] Blast furnace slag, fly ash, and inert mineral admixtures are continuously dried in a drying equipment at 85℃ for 24 hours before use.
[0060] Antioxidant 1010, chemical name pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid], CAS number 6683-19-8.
[0061] Example 1 A low-carbon curing agent for deep mixing piles in soft soil foundations, comprising the following raw materials by weight: 3 parts composite cement, 60 parts blast furnace slag, 10 parts fly ash, 5 parts composite gypsum, and inert mineral admixture (heavy calcium carbonate powder, specific surface area 396 m²). 2 1 part ( / kg), 0.02 parts compound activator, and 0.01 parts compound admixture; The composite cement is composed of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine; the mass ratio of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine is 0.6:0.2:0.2:0.0001.
[0062] Composite gypsum is composed of hemihydrate gypsum and fluorogypsum, with a mass ratio of hemihydrate gypsum to fluorogypsum of 0.1:0.9.
[0063] The composite activator is composed of sodium sulfate, red mud and sodium silicate, with a mass ratio of sodium sulfate, red mud and sodium silicate of 0.05:0.9:0.05.
[0064] Preparation method of low-carbon solidifying agent for deep mixing piles in soft soil foundation: A low-carbon curing agent for deep mixing piles in soft soil foundations is obtained by ball milling composite cement, blast furnace slag, fly ash, composite gypsum, inert mineral admixtures, composite activators, and composite additives (at a rate of 100 r / min for 10 min).
[0065] Example 2 A low-carbon curing agent for deep mixing piles in soft soil foundations, comprising the following raw materials by weight: 9 parts composite cement, 50 parts blast furnace slag, 12.5 parts fly ash, 7.5 parts composite gypsum, and inert mineral admixture (heavy calcium carbonate powder, with a specific surface area of 396 m²). 2 5 parts ( / kg), 1.25 parts compound activator and 0.05 parts compound admixture; The composite cement is composed of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine; the mass ratio of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine is 0.8:0.1:0.1:0.00025.
[0066] Composite gypsum is composed of hemihydrate gypsum and fluorogypsum, with a mass ratio of hemihydrate gypsum to fluorogypsum of 0.2:0.8.
[0067] The composite activator is composed of sodium sulfate, red mud and sodium silicate, with a mass ratio of sodium sulfate, red mud and sodium silicate of 0.2:0.7:0.1.
[0068] The preparation method of the low-carbon curing agent for deep mixing piles in soft soil foundation is the same as in Example 1.
[0069] Example 3 A low-carbon curing agent for deep mixing piles in soft soil foundations, comprising the following raw materials by weight: 15 parts composite cement, 70 parts blast furnace slag, 20 parts fly ash, 10 parts composite gypsum, and inert mineral admixture (heavy calcium carbonate powder, specific surface area 396 m²). 2 10 parts ( / kg), 2.5 parts compound activator, and 0.08 parts compound admixture; The composite cement is composed of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine; the mass ratio of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine is 0.9:0.05:0.05:0.0005.
[0070] Composite gypsum is composed of hemihydrate gypsum and fluorogypsum, with a mass ratio of hemihydrate gypsum to fluorogypsum of 0.3:0.7.
[0071] The composite activator is composed of sodium sulfate, red mud and sodium silicate, with a mass ratio of sodium sulfate, red mud and sodium silicate of 0.4:0.6:0.01.
[0072] The preparation method of the low-carbon curing agent for deep mixing piles in soft soil foundation is the same as in Example 1.
[0073] Comparative Example 1 Compared with Example 1, this comparative example does not include triethanolamine modified with composite acid in the low-carbon curing agent, while the other raw materials are the same as in Example 1.
[0074] The curing agent is prepared in the same way as in Example 1.
[0075] Comparative Example 2 Compared with Example 1, this comparative example does not contain phosphorous acid in the composite acid-modified triethanolamine, while the other raw materials are the same as in Example 1.
[0076] The curing agent is prepared in the same way as in Example 1.
[0077] Comparative Example 3 Compared with Example 1, this comparative example does not contain any composite additives, but the other raw materials are the same as in Example 1.
[0078] The curing agent is prepared in the same way as in Example 1.
[0079] Comparative Example 4 Compared with Example 1, this comparative example does not include fatty alcohol polyoxyethylene ether in the composite additive, while the other raw materials are the same as in Example 1.
[0080] The curing agent is prepared in the same way as in Example 1.
[0081] Comparative Example 5 Compared with Example 1, this comparative example does not include polyacrylamide in the composite additive, while the other raw materials are the same as in Example 1.
[0082] The curing agent is prepared in the same way as in Example 1.
[0083] Comparative Example 6 In this comparative example, P·O 42.5 ordinary Portland cement was used as the consolidating agent for the mixing pile. Other methods and steps were the same as in Example 1, and will not be repeated here.
[0084] Comparative Example 7 This comparative example uses a commercially available low-carbon consolidating agent (produced by Jinan Mingde New Building Materials Co., Ltd.) as the consolidating agent for the mixing piles. Other methods and steps are the same as in Example 1, and will not be repeated here.
[0085] The properties of the curing agents prepared in Examples 1-3 and Comparative Examples 1-7 were characterized: The preparation, curing, and unconfined compressive strength testing of laboratory specimens were carried out in accordance with the "Specification for Mix Proportioning Design of Cement and Soil" (JGJ / T 233-2011); the fluidity of the cement paste was carried out in accordance with the "Test Method for Homogeneity of Concrete Admixtures" (GB / T 8077-2023); and the initial setting time was carried out in accordance with the "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" (GB / T1346-2024).
[0086] The method for testing the bleeding volume of the paste is as follows: Use an open metal bucket with a height of 150 cm and a diameter of 100 cm. Weigh (500±5) g of the well-mixed paste. Place the metal bucket in an undisturbed environment and let it stand for 5 minutes. Then, use a dropper to suck out the upper layer of exudate and weigh it. The result should be retained to one decimal place.
[0087] Water immersion mass loss rate: (mass of specimen after water curing to the predetermined age - mass of specimen before water curing) / mass of specimen before water curing × 100%, the result is rounded to two decimal places.
[0088] The performance test results of the curing agent are shown in Table 1.
[0089] Table 1 Performance test results of the curing agent
[0090] The results of unconfined compressive strength of laboratory specimens and field specimens, as well as the water immersion mass loss rate of laboratory specimens, are shown in Table 2.
[0091] Table 2. Unconfined compressive strength properties of laboratory specimens and field specimens, and results of water immersion mass loss rate of laboratory specimens.
[0092] Note: In Table 2, the " / " in the comparative examples indicates that the actual data could not be detected due to the low intensity.
[0093] Table 1 shows that, compared with the comparative example, the slurry prepared by the low-carbon curing agent for deep mixing piles in soft soil foundations in Examples 1-3 exhibited good fluidity in the first 60 minutes, and no obvious segregation or bleeding occurred after standing for 10 minutes. Furthermore, the initial setting time of the low-carbon curing agent for deep mixing piles in soft soil foundations in Examples 1-3 was shorter, indicating that using the low-carbon curing agent for deep mixing piles in Examples 1-3 to prepare mixing piles can improve the early mechanical properties of the mixing piles while ensuring construction time. However, in the comparative example without the addition of key components, the bleeding amount and setting time of the curing agent showed varying degrees of decrease. Table 2 shows that, compared with cement and commercially available binders, the mixing piles prepared using the low-carbon curing agent for deep mixing piles in soft soil foundations in Examples 1-3 exhibited superior mechanical properties under both laboratory and field construction conditions. Meanwhile, the specimens prepared using the low-carbon curing agent for deep mixing piles in soft soil foundations in Examples 1-3 showed a smaller water immersion mass loss rate, indicating that the low-carbon curing agent used in Examples 1-3 for deep mixing piles in soft soil foundations has better water seepage resistance.
[0094] Example 4 The construction method of low-carbon curing agent for deep mixing piles in soft soil foundation includes the following steps: S1. The low-carbon curing agent for deep mixing piles in soft soil foundations is mixed with water to form a slurry by feeding materials according to the preset ratio through an automatic metering system. S2. Move the pile driver to the pile position, start the mixing drill, and inject grout into the borehole through the grout delivery device while drilling. When the drill bit of the mixing drill reaches the designed depth, rotate it in the opposite direction to lift the drill bit, and inject grout into the borehole through the grout delivery device while lifting. S3. When the drill bit of the mixing drill reaches the top of the pile, the slurry delivery device is turned off, and the mixing drill resumes drilling for mixing. When the drill bit of the mixing drill reaches the designed depth, it is rotated in the opposite direction to lift the drill bit until it reaches the top of the pile. S4. After the single pile construction is completed, move the machine to the next pile position and cycle through "drilling down and spraying grout - lifting and spraying grout - drilling down and mixing - drilling up and mixing".
[0095] In step S1, the mass ratio of water to the low-carbon curing agent used for deep mixing piles in soft soil foundation is (0.5~0.8):1; In step S1, the method for mixing the low-carbon curing agent for deep mixing piles in soft soil foundations with water to form a slurry includes: The low-carbon curing agent for deep mixing piles in soft soil foundations is dispersed in 50-60% of the total water volume. After stirring, the remaining water is added, and stirring is continued to obtain the slurry. The stirring and continuous stirring rate is 200-300 r / min; the stirring time is not less than 2 min; and the continuous stirring time is not less than 2 min.
[0096] In step S2, the pressure of the injected slurry is 1.0~3.0 MPa.
[0097] In step S2, the drilling speed of the drill bit of the mixing drill is 0.5~1.0 m / min.
[0098] In step S2, the drill bit of the mixing drill is lifted at a rate of 0.5~1.0 m / min.
[0099] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A low-carbon curing agent for deep mixing piles in soft soil foundations, characterized in that, Its raw materials, by weight, include: The composition includes 3-15 parts of composite cement, 30-70 parts of blast furnace slag, 5-20 parts of fly ash, 5-10 parts of composite gypsum, 0.01-10 parts of inert mineral admixture, 0.02-2.5 parts of composite activator, and 0.01-0.08 parts of composite additive. The composite cement is composed of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine; the composite acid-modified triethanolamine is triethanolamine modified with phosphorous acid and sebacic anhydride; the mass ratio of P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid-hardening sulfoaluminate cement, and composite acid-modified triethanolamine is (0.6~0.9):(0.01~0.3):(0.05~0.2):(0.0001~0.0005). The method for preparing the composite acid-modified triethanolamine includes: (1) Triethanolamine, p-toluenesulfonic acid and hydroquinone are dispersed in toluene, and sebacic anhydride is added in batches to carry out esterification reaction; (2) After the esterification reaction is completed, add phosphorous acid, distill under reduced pressure, and collect the fraction at 130~140℃; after cooling to room temperature, filter and collect the filtrate; remove the solvent, dry and obtain the composite acid modified triethanolamine; The preparation method of composite cement includes: ball milling composite cement comprising P·O 42.5 ordinary Portland cement, P·O 52.5 ordinary Portland cement, 42.5 rapid hardening sulfoaluminate cement and composite acid-modified triethanolamine to obtain composite cement; The composite gypsum is composed of hemihydrate gypsum and fluorogypsum; the mass ratio of hemihydrate gypsum to fluorogypsum is (0.1~0.3):(0.7~0.9). The inert mineral admixture is heavy calcium carbonate powder; The composite activator is composed of sodium sulfate, red mud, and sodium silicate; the mass ratio of sodium sulfate, red mud, and sodium silicate is (0.05~0.4):(0.6~0.9):(0.01~0.15). The composite admixture includes polycarboxylic acid, fatty alcohol polyoxyethylene ether, and polyacrylamide; the mass ratio of polycarboxylic acid water-reducing agent, fatty alcohol polyoxyethylene ether, and polyacrylamide is (0.8~0.95):(0.01~0.1):(0.01~0.1). The preparation methods of composite admixtures include: Under nitrogen protection, antioxidant 1010 was added to fatty alcohol polyoxyethylene ether and stirred until dissolved. Then phosphoric acid was added in batches and stirred at 55~65℃ until the system became a uniform viscous liquid. Water was added to the system and stirred until homogeneous. The monoester content was measured to be ≥60%, and the pH of the system was adjusted to 6.5~7.
5. The liquid product was collected by vacuum distillation and spray-dried to obtain a powdered enhanced wetting agent. A composite additive is obtained by mixing polycarboxylate superplasticizer, powdered reinforcing wetting agent and polyacrylamide.
2. The low-carbon curing agent for deep mixing piles in soft soil foundations as described in claim 1, characterized in that, The blast furnace slag is of grade S95 or higher, with a combined SiO2 and CaO content greater than 80%. The fly ash is secondary fly ash, with the sum of SiO2, Al2O3 and Fe2O3 content ≥70.0%.
3. The method for preparing the low-carbon solidifying agent for deep mixing piles in soft soil foundations as described in claim 1 or 2, characterized in that, Includes the following steps: A low-carbon curing agent for deep mixing piles in soft soil foundations is obtained by ball milling composite cement, blast furnace slag, fly ash, composite gypsum, inert mineral admixtures, composite activators, and composite additives.
4. The construction method of the low-carbon solidifying agent for deep mixing piles in soft soil foundation as described in claim 1 or 2, characterized in that, Includes the following steps: S1. The low-carbon curing agent for deep mixing piles in soft soil foundations is mixed with water to form a slurry by feeding materials according to the preset ratio through an automatic metering system. S2. Move the pile driver to the pile position, start the mixing drill, and inject grout into the borehole through the grout delivery device while drilling. When the drill bit of the mixing drill reaches the designed depth, rotate it in the opposite direction to lift the drill bit, and inject grout into the borehole through the grout delivery device while lifting. S3. When the drill bit of the mixing drill reaches the top of the pile, the slurry delivery device is turned off, and the mixing drill resumes drilling for mixing. When the drill bit of the mixing drill reaches the designed depth, it is rotated in the opposite direction to lift the drill bit until it reaches the top of the pile. S4. After the single pile construction is completed, move the machine to the next pile position and cycle through "drilling down and spraying grout - lifting and spraying grout - drilling down and mixing - drilling up and mixing".
5. The construction method as described in claim 4, characterized in that, In step S1, the mass ratio of water to the low-carbon curing agent used for deep mixing piles in soft soil foundation is (0.5~0.8):1; In step S1, the method for mixing the low-carbon curing agent for deep mixing piles in soft soil foundations with water to form a slurry includes: The low-carbon curing agent used for deep mixing piles in soft soil foundations is dispersed in 50-60% of the total water volume, and the remaining water is added after stirring. The mixture is stirred continuously to obtain slurry. The stirring and continuous stirring rate is 200~300 r / min; the stirring time is not less than 2 min; the continuous stirring time is not less than 2 min.
6. The construction method as described in claim 4, characterized in that, In step S2, the pressure of the injected slurry is 1.0~3.0 MPa; In step S2, the drilling speed of the mixing drill bit is 0.5~1.0 m / min; In step S2, the drill bit of the mixing drill is lifted at a rate of 0.5~1.0 m / min.
Citation Information
Patent Citations
Preparation method of modified triethanolamine
CN110204449A
Curing agent for deep mixing pile of soft soil foundation as well as preparation method and application of curing agent
CN120058326A
